PENGENDALIAN KUALITAS PROSES FABRIKASI PANEL KOMPOSIT AMPAS KOPI MENGGUNAKAN METODE TAGUCHI - Raihaan .; Yuni Hermawan; Ahmad Adib Rosyadi; Mahros Darsin; Robertus Sidartawan (Jurusan Teknik Mesin, 2023)
The use of composites has touched various fields, for example in land, sea and air transportation and household appliances. The coffee pulp particle composite panel produces new properties that are unique and affect the characteristics of mechanical strength, especially tensile strength and bending strength [7]. The standard for making good coffee pulp composite panels and producing optimal strength needs to be done [4]. To reduce the air bubbles created, a degasification process needs to be done [5]. In making composites using the hand lay-up method has several main parameters for its tensile strength, where the main parameters used are stirring speed 515 rpm, 915 rpm, 1430 rpm; duration of degasification 7.5 minutes, 10 minutes, 12.5 minutes; degasification pressure -30 kPa, -60 kPa, -90 kPa. The optimal results obtained were 24.88 MPa with an increase of 23.18% from previous studies using the initial combination.